FOREIGN EXPERIENCE IN CONTROL OF THE LOCAL OMBUDSMAN OVER THE ACTIVITIES OF LOCAL GOVERNMENT BODIES AND THE POSSIBILITY OF ITS APPLICATION IN UKRAINE - Ібрагімов, Ельшад (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: вased on the analysis of the experience of foreign countries and existing theoretical developments, the article argues the expediency and effectiveness of the activities of the institution of local ombudsman in Ukraine. The Ombudsman is seen as an additional means of identifying and eliminating violations of the law that were not detected in the course of administrative supervision and internal control. The main provisions that determine the legal status of the ombudsman in foreign countries are highlighted. Methods: the research was carried out using such methods as analysis and comparison, synthesis. The method of analysis and comparison was applied in the study of scientific developments of the mechanism of public control over the activities of local authorities in foreign countries, the feasibility and effectiveness of the institution of local ombudsmen in Ukraine. Using the synthesis method, a mechanism for public control over the activities of local authorities in foreign countries has been established. Results: it is advisable to introduce the institution of the human rights ombudsman of the territorial community as an independent official authorized to consider and process complaints from citizens about the actions and inaction of local self-government bodies and their officials.Discussion: highlights the main provisions that determine the legal status of the Ombudsman in foreign countries. According to the author of the article, the institution of the human rights ombudsman of the territorial community should be an additional means of control over the rule of law, which functions both for the citizen and for public authorities. Such control is carried out by receiving and considering complaints from citizens who believe that their rights are violated by decisions, actions or inaction of local authorities. In addition, it is advisable to provide for the right of the Ombudsman to initiate proceedings on his own initiative in the event of a violation of the law in the activities of local self-government bodies, which may lead to a violation of the rights of citizens. The Ombudsman should be empowered to monitor both the legality and the appropriateness of the actions of local authorities. The importance of the institution of the local ombudsman for ensuring the rule of law lies in the fact that by exercising these powers, it can contribute to the elimination of systemic violations of regulations that local authorities allow and concerning the rights and freedoms of persons living in the territory of the corresponding administrative-territorial unit.